Fifty years of hemodialysis access literature: The fifty most cited publications in the medical literature. (February 2018) - Skripochnik, Edvard; O'Connor, David J; Trestman, Eric B; Lipsitz, Evan C; Scher, Larry A
Objectives: The modern era of hemodialysis access surgery began with the publication in 1966 by Brescia et al. describing the use of a surgically created arteriovenous fistula. Since then, the number of patients on chronic hemodialysis and the number of publications dealing with hemodialysis access have steadily increased. We have chronicled the increase in publications in the medical literature dealing with hemodialysis access by evaluating the characteristics of the 50 most cited articles. Methods: We queried the Science Citation Index from the years 1960–2014. Articles were selected based on a subject search and were ranked according to the number of times they were cited in the medical literature. Results: The 50 most frequently cited articles were selected for further analysis and the number of annual publications was tracked. The landmark publication by Dr Brescia et al. was unequivocally the most cited article dealing with hemodialysis access (1109 citations). The subject matter of the papers included AV fistula and graft (9), hemodialysis catheter (9), complications and outcomes (24), and other topics (8). Most articles were published in nephrology journals (33), with fewer in surgery (7), medicine (7), and radiology (3) journals. Of the 17 journals represented, Kidney International was the clear leader, publishing 18 articles. There has been an exponential rise in the frequency of publications regarding dialysis access with 42 of 50 analyzed papers being authored after 1990. Conclusion: As the number of patients on hemodialysis has increased dramatically over the past five decades, there has been a commensurate increase in the overall number of publications related to hemodialysis access